Flexible equality: Men and women in employment in Japan - Karen A. Shire; Jun Imai (Gerhard-Mercator-Universität Duisburg, Institut für Ostasienwissenschaften, 2000)
Changes in the structure and regulation of employment in Japan differentially impact men and women. The labor force participation of Japanese women is increasing, but women's employment is concentrated in relatively deregulated and flexible forms of non-standard and precarious employment. Women and men have relatively equal levels of unemployment at present, but the flexibility which characterizes part-time and temporary work lands women into the ranks of the unemployed throughout their life course, while men are more likely to experience unemployment at the entry and exit points to the labor market. Unemployment measures are directed mainly at alleviating the sources of male unemployment. Employment deregulation in Japan embodies varying degrees of re-regulation depending on the gender composition of work types. Part-time work is undertaken primarily by women, and remains relatively deregulated and unprotected. Temporary work regulations vary according to whether the occupations are typically performed by women (deregulated temporary work) or men (tightly regulated temporary work). Working hours have been deregulated for both men and women, but coupled with the deregulation of temporary work in female-dominated occupations, the change poses a greater disadvantage for women. The recent reform of the Equal Employment Opportunity Law in Japan, while responding in part to social demands for strengthening the regulation of equality, remains unenforceable. The analysis concludes that rather than more equality in employment, recent Japanese developments point to the institutional embedding of a gender segmented labor market, with men continuing in relatively protected and regulated standard employment and women relegated to flexible and deregulated employment.
Keywords: 330; employment; flexibility; regulation; labor; gender; Japan; Frauenerwerbstätigkeit; Arbeitsmarktdiskriminierung; Ungeschützte Beschäftigung; Arbeitslosigkeit; Geschlecht; Japan